Asymmetric Supercapacitors Based on Activated‐Carbon‐Coated Carbon Nanotubes. Issue 3 (9th January 2015) - Shi, Kaiyuan; Zhitomirsky, Igor
Abstract A new method is developed for the fabrication of asymmetric supercapacitor devices containing fibrous electrode materials. The approach is based on the synthesis of uniform polypyrrole (PPy) coatings on multiwalled carbon nanotubes (MWCNT), which were used for the fabrication of MWCNTs coated with N‐doped activated carbon (N‐AC). The N‐AC‐MWCNT electrodes show good electrochemical performance in positive and negative potential windows. The electrochemical performance of positive electrodes is further enhanced by the development of MnO2‐coated N‐AC‐MWCNT. In this approach, the problem of MWCNT degradation in the reaction with KMnO4 is avoided by the use of a sacrificial N‐AC layer, which allows a relatively high mass content of MnO2 in the final material. The approach offers the advantages of small size of MnO2 nanoparticles, good electrical contact of MnO2 and MWCNT and fibrous microstructure of the material. Testing results show a remarkably high specific capacitance of 6.29 F cm−2 (311.7 F g−1) at a mass loading of 20 mg cm−2. The important finding is the possibility to fabricate asymmetric devices, which show a specific capacitance of 2.19 F cm−2 (62.7 F g−1) in a voltage window of 1.9 V in aqueous Na2SO4 electrolyte, an energy density of 26.4 mWh g−1 and a power density of 1.7 W g−1. The electrodes and devices show good capacitance retention at high charge–discharge rates and good cycling stability. The asymmetric capacitors developed herein are promising for practical energy‐storage applications.